Incidence rate and patient characteristics of severe hypoglycemia in treated type 2 diabetes mellitus patients in Japan: Retrospective Diagnosis Procedure Combination database analysis. Issue 4 (16th January 2018) - Ikeda, Yuika; Kubo, Takekazu; Oda, Eisei; Abe, Machiko; Tokita, Shigeru
Abstract : Incidence rate and risk factors of severe hepoglycemia in treated type 2 diabetes mellitus patients in Japan were evaluated using medical database. Abstract: Aims/Introduction: To evaluate the incidence rate of and identify factors associated with severe hypoglycemic episodes in patients with treated type 2 diabetes mellitus. Materials and Methods: Using Diagnosis Procedure Combination hospital‐based medical database, we carried out a retrospective cohort study to assess the incidence rate of severe hypoglycemia in treated type 2 diabetes mellitus patients. We evaluated the associations between severe hypoglycemia and age, sex, complications, and current use of insulin or sulfonylurea (SU) in a nested case–control study. Results: Of 166, 806 eligible patients, 1, 242 had episodes of severe hypoglycemia during the observational period. The incidence rate of the first hypoglycemic events was 3.70/1, 000 patient years. Based on the nested case–control analysis, age was associated with hypoglycemic events with adjusted odds ratios (ORs) of 1.64 or 65–74‐year‐old patients and 3.79 for ≥75‐year‐old patients in comparison with 20–64‐year‐old patients. Comorbidities, such as cognitive impairment, cancer, macrovascular disease and diabetic complications (retinopathy, nephropathy and neuropathy), were associated with severe hypoglycemia, with adjusted ORs ranging from 1.25 to 3.80. Severe hypoglycemic events also increased in patients with current use of both SU and insulin, either SU or insulin, with adjusted ORs of 18.36, 6.31 or 14.07, respectively, compared with patients with other antihyperglycemic agents. In patients with an SU glimepiride, adjusted ORs increased dose‐dependently from 3.65 (≤1 mg) to 13.34 (>2 mg). Conclusions: The incidence rate of severe hypoglycemia in this cohort was 3.70/1, 000 patient years. Age, cognitive impairment, cancer, diabetic complications, current use of insulin + SU and SU dosage were identified as risk factors for severe hypoglycemia.